(untitled) (Baghdad Science Journal, 2024)
Solanum melongena, the plant used as a food and medical remedy known as eggplant, has anti-inflammatory, antioxidant, and anti-cancer properties. It is one of the vegetables that is most widely cultivated worldwide and has a wide range of vegetable sizes, colors, and shapes. This study looked at thirteen chemical compounds in the plant using gas chromatography and mass spectrometric detection (GC-MS). The gathered information verified that the object included thirteen chemical components, likes 2 — pentanone-4-hydroxy 4- methyl% 2.30, 1,3-dioxolane-4-methanol %0.17, formic acid %0.86, methenamine-methoxy %4.528,1,2,3-propanetriol (glycerin) %40.86, tetradecane%0.16, hexadecane%0.27, octadecane %0.16, myristic acid %3.14, nonadecane%0.44,9,12-octadecadienoic acid linolenic acid %0.43, oleic acid%2.36, and octacosane %0.62. These substances have been found to have strong anti-free radical properties, with eggplant powder’s antioxidant activity standing out. These compounds are chemically characterized as antioxidants. Using the effective concentration EC50 method, the EC50 of eggplant powder (Solanum melongena) was 209 µg/mL. The extracts’ DPPH-free radical scavenging activity was assessed, and it increased with concentration, going from 4.8828 (µg/mL) to 1250 (µg/mL). The radical scavenging activity of eggplant powder (Solanum melongena) increased from 0.87 to 76.04 indicating a high correlation between concentration and radical scavenging activity. The composition of the mineral elements in the powdered eggplant was ascertained using an (ICP/OES Perkin Elmer 2100), (Inductivity Coupled Plasma Emission Spectrometer). Al, Cu, Mn, Fe, Ba, Cr, Co, and Ni were found to be the principal minerals with high concentrations. However, the concentrations of (Cd 0.8974 µg/L and Pb not detectable) were incredibly low.